PENGARUH PEMBIAYAAN WARUNG MIKRO BSM TERHADAP PERKEMBANGAN USAHA NASABAH DI KOTA SUBULUSSALAM (STUDI KASUS PADA BSM KCP. SUBULUSSALAM, ACEH SINGKIL): STAISAR Aceh Singkil - Muflihatul Fauza (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2020)
Abstract This study aims to determine the effect of micro shop financing in BSM KCP Subulussalam on the development of micro-businesses in the city of Subulussalam, how big is the influence of micro shop financing on development and to find out differences in customer income before and after getting financing. The research methodology used is field research using a quantitative approach. The sample used is the customer of the micro shop BSM KCP Subulussalam on micro-business financing products. The data collection instrument used primary data and secondary data. The analytical tools used in this study are the t test, the coefficient of determination, the simple linear regression model tested with the help of the SPSS version 16 program and manual calculations, and the average difference test that is calculated manually. The results of the research conducted indicate that there is an effect of micro shop financing provided by BSM KCP Subulussalam on the development of micro-businesses. The level of significance of the financing for micro stalls in BSM KCP Subulussalam is 0.000, smaller than 0.05 with tcount (8.042)> ttable (1.684), the determinant coefficient (R2) in this study is 0.618. This means that 61.8% of the development of the customer's micro business is influenced by the financing of the micro shop BSM KCP Subulussalam and the remaining 38.2% is influenced by other factors. The simple linear regression equation generated in this study is PUM = 9.659 + 0.715 PWM. And there is an effect of micro shop financing on increasing customer income with tcount> t table, namely 7.66> 1.684. The conclusion in this study is that there is a significant and positive influence between the financing of the micro shop BSM KCP Subulussalam with the development of micro-businesses. Keywords: Financing, Micro Stalls